Production of highly immunogenic/ hydrophilic regions of naiha gene using assembly pcr - Shobana Devi, Murugiah (Universiti Sains Malaysia, 2008)
Influenza pandemics resemble major natural disasters. According to the list that has been published by World Health Organization (WHO), the number of total cases of avian influenza is 387cases and 245 of those cases had cause deaths. The number of total cases and deaths shows that there was an increased pandemic threat. Justifiably, this had caused the world-wide public concern and it also explains the need for vaccine production for this Avian Influenza. The main antigenic determinants of influenza A and B viruses are the haemagglutinin (HA) and neuraminidase (NA) transmembrane glycoproteins. The activities ofHA and NA are functionally linked and make them the most potential candidates for the avian influenza disease vaccine in human. In this study, highly immunogenic/ hydrophilic regions ofNAIHA gene was constructed using assembly PCR. The synthetic gene was constructed using assembly PCR and cloned into pCR®2.1-TOPO®vector. The recombinant plasmid isolated from the colony was send for sequencing and alignment result shows that there were three errors in the synthetic gene being constructed. PCR-based site directed mutagenesis technique must be performed to repair those errors. Although the synthetic gene was not developed as originally planned, this study has generated data that would be useful towards achieving that goal in the future.